Pengaruh Game Online Mobile Legend Terhadap Prestasi Belajar Siswa Kelas VII Pada Mata Pelajaran IPS SMP Al-Falah Kota Bekasi - Sinta Fitriani; Rita Aryani; Uza Sukmana (Indo Publishing, 2025)
This study aims to determine the extent of the influence of the online game Mobile Legends on student achievement in social studies at Al-Falah Junior High School in Bekasi City. It also aims to provide an overview of the negative impact of online games on student achievement.This study used an associative quantitative research method. The population was 242 seventh-grade junior high school students, with a sample of 151 students using total sampling. Data collection techniques and instruments used were a questionnaire with a Likert scale, observation, and documentation. Descriptive analysis was used to analyze the data. Furthermore, to determine the extent of the influence of online games, a regression analysis was conducted on the two data sets. The results showed that, on average, students' addiction to playing the online game Mobile Legends affected their academic achievement, with the average academic achievement score being 81.75. The magnitude of the negative impact of online games, after being tested using a linear regression test, revealed that 2.7% of the influence on student academic achievement was due to online game addiction, with the remaining 97.3% being influenced by other factors.